3D printing of powdered activated carbon monoliths: Effect of structuring on physicochemical and mechanical properties and its influence on the adsorption performance. (December 2022) - Rangel‑Sequeda, Jair Fernando; Loredo‑Cancino, Margarita; Águeda Maté, Vicente Ismael; De Haro‑Del Rio, David Alejandro; Dávila-Guzmán, Nancy Elizabeth
Abstract: Herein, a methodology for 3D printing of activated carbon powders in monolithic form using direct ink writing and carboxymethylcellulose as binder is reported, along with the effect on their physicochemical and mechanical properties. Monoliths with different wall diameters (0.42, 0.62, and 0.82 mm) and infill percentages (30%, 50%, and 70%) were designed and manufactured. The monoliths were heat-treated under a nitrogen atmosphere at 400 °C and 600 °C to remove the volatile material from the binder used. The monoliths showed a decrease in dimension of less than 8% from their designed values, attributed to the volatilization of water present in the binder solution in the drying and heat-treatment process. The printed monoliths presented pore distributions similar to those of their powdered counterparts. The isoelectric point of the monoliths increased relative to that of the powdered material and became more basic as the heat treatment temperature increased. The monoliths presented compressive strengths from 0.58 to 3.53 MPa. The analysis of variance of the compressive strength showed that the wall diameter and temperature are the most influential treatment parameters. The printed monoliths exhibited similar CO2 adsorption capacity (0.37 mol Kg −1 at 10 kPa and 25 °C) compared to the powder precursor. Fixed bed tests demonstrated that the 3D printed monoliths enhanced the mass transfer compared to conventionally extruded pellets with same wall diameter. Graphical Abstract: ga1